Development of Urban Forest in Indonesia - Endes N Dahlan (Department of Forest Resources Conservation and Ecotourism - IPB University, 1992)
Urban forest is a unique forest resource. It can be used to overcome several problems which often appear in the city. There are more than 19 advantages of urban forest. To encourage the construction and development of urban forest in the cities in Indonesia, supporting facilities from government are needed.